Tadhkirat al-shuʿarāʾ - Samarqandī, 'Sulṭān' Muḥammad Muṭribī (Miras Maktoob, ISBN: 9789004365452., 2019)
Born into a family of scholars and literati in Samarqand, Muḥammad 'Sulṭān' Muṭribī Samarqandī (d. 1040/1630) regarded himself as a descendant of Arghūn Āqā (d. 673/1275), viceroy of the Mongols in Khurāsān. He received a broad education with an emphasis on literature and music, first in Samarqand and then in Bukhara. His major teacher in literature in Bukhara was Ḥasan Nithārī Bukhārāʾī (d. 1004/1596). Muṭribī is well-known for his Khāṭirāt , recollections of his highly-polished conversations with the Mughal emperor Jahāngīr (d. 1627), which took place during his visit to him in Lahore in 1036/1626. The other work for which he is known is his Persian Tadhkirat al-shuʿarāʾ , a biographical dictionary of some 343 poets, emirs, and sultans, mainly from Transoxania and Badakhshān. A unique source of information on its time and modelled on a similar work by his teacher, it is based on his direct acquaintance with most of the people it describes.